Адміністративно-правові засади контролю за дотриманням законодавства про азартні ігри та лотереї - Шатрава, С. О.; Shatrava, S. O. (Наукові записки [Центральноукр. держ. пед. ун-ту імені Володимира Винниченка]. Сер.: Право. - 2022. - Вип. 13. - С. 254-258, 2022)
В статті доведено, що на сьогоднішній день маємо сформовану відповідну систему органів публічної адміністрації, які наділені контрольними (наглядовими) повноваженнями у сфері організації та проведення азартних ігор та лотерей. Особливе місце відводиться Комісії з регулювання азартних ігор та лотерей, яка наділена відповідними дозвільними повноваженнями у сфері організації та проведення азартних ігор та лотерей. Комісія з регулювання азартних ігор та лотерей, як центральний орган виконавчої влади зі спеціальним статусом наділена широким спектром контроль-наглядових повноважень, що має свій прояв у застосуванні всіх заходів адміністративного примусу до відповідних суб’єктів господарської діяльності, а саме здійснення заходів адміністративного попередження, припинення та застосування санкцій до порушників. Виокремлено основні контрольно-наглядові повноваження Комісії з регулювання азартних ігор та лотерей у досліджуємій сфері суспільних відносин шляхом: 1) контролю наявності передбачених законом ліцензій; 2) перевірки додержання організатором азартних ігор ліцензійних умов; 3) контролю за додержанням організаторами азартних ігор вимог законодавства, стандартів та нормативно-правових актів у сфері організації та проведення азартних ігор; 4) моніторингу діяльності організаторів азартних ігор з використанням Державної системи онлайн-моніторингу.

The article proves that today we have an appropriate system of public administration bodies that are empowered with control (supervisory) powers in the field of organizing and conducting gambling and lotteries. A special place is given to the Gambling and Lottery Regulation Commission, which is endowed with relevant authorization powers in the field of organizing and conducting gambling games and lotteries. The Commission for the Regulation of Gambling and Lotteries, as a central body of executive power with a special status, is endowed with a wide range of control and supervisory powers, which is manifested in the application of all measures of administrative coercion to the relevant subjects of economic activity, namely, the implementation of administrative warning measures, termination and application of sanctions to violators. On the basis of the norms of the current legislation, the main control and supervisory powers of the Commission for the Regulation of Gambling and Lotteries in the researched sphere of public relations are distinguished by: 1) control of the presence of licenses provided for by law; 2) verification of compliance by the gambling organizer with license conditions; 3) control over compliance by the organizers of gambling with the requirements of legislation, standards and regulatory acts in the field of organizing and conducting gambling; 4) monitoring activities of gambling organizers using the State online monitoring system. In exercising its powers, the Commission for the Regulation of Gambling and Lotteries must adhere to the main principle of state policy in the field under investigation, which is the fight against gambling addiction (ludomania), since some profits from gambling and lotteries will not contribute to the normal development of society and man.

В статье доказано, что на сегодняшний день сформирована соответствующая система органов публичной администрации, наделенные контрольными (надзорными) полномочиями в сфере организации и проведения азартных игр и лотерей. Особое место отводится Комиссии по регулированию азартных игр и лотерей, которая наделена соответствующими разрешительными полномочиями в сфере организации и проведения азартных игр и лотерей. Комиссия по регулированию азартных игр и лотерей, как центральный орган исполнительной власти со специальным статусом наделена широким спектром контроль-надзорных полномочий, что имеет свое проявление в применении всех мер административного принуждения соответствующих субъектов хозяйственной деятельности, а именно осуществление мер административного предупреждения, прекращения и применение санкций к нарушителям.
Administrative and legal principles of control of compliance with the legislation on gambling and lotteries
Keywords: Комісія з регулювання азартних ігор та лотерей; адміністративно-правові засади; азартна гра; лотерея; контроль; нагляд; ліцензійні умови; моніторинг; санкції; Gambling and Lottery Regulation Commission; administrative and legal framework; gambling; lottery; control; supervision; license conditions; monitoring; sanctions; Комиссия по регулированию азартных игр и лотерей; административно-правовые основы; азартная игра; надзор; лицензионные условия; мониторинг; санкции